ECOSOPHY ISLAM: STUDI TEMATIS-KONTEKSTUAL NILAI-NILAI ETIKA LINGKUNGAN DALAM ISLAM (THE ECOSOPHY OF ISLAM: A Thematic and Contextual Study of The Environmental Ethics Values in Islam) - Rusmadi Rusmadi (Balai Penelitian dan Pengembangan Agama Semarang, 2016)
Monotheistic religions including Islam are often accused as the main supporter of anthropocentrism that is not friendly toward environment. This is because monotheistic religions give more priority toward human beings who are placed at higher level than other creatures. Monotheistic religions mention that environment is created for supporting human’s life; therefore this notion encourages people to exploit natural resources. This study aims to expose the concept of environmental nurture from Islamic perspective. This research employs thematic-contextual analyses approach to examine Qur’anic verses. The Qur’an verses related to cosmic and human beings with environment were collected and systematized. Then, it is described the views on the ethical Islam regarding the environment as the basis of environmental ethic. Results of this study rebutted the accuse and stigmatization on religion as the supporter of anthropocentrically ethic, and it completes the approach on the environmental management that have already been known in the study of environment, namely arranging and watching approach, economical environment approach, and especially a voluntary arranged approach.